2021
DOI: 10.3390/ani11092698
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Enzymes Influenced Eimeria-Induced Changes in Cecal Fermentation Profile and Gene Expression of Nutrient Transporters in Broiler Chickens

Abstract: Two 21-day experiments were conducted to investigate the effects of exogenous enzymes on growth performance, tight junctions, and nutrient transporters, jejunal oligosaccharides and cecal short-chain fatty acids (SCFA) of broiler chickens challenged with mixed Eimeria. Two different basal diets: high fiber-adequate protein (HFAP; Expt. 1) or low fiber-low protein (LFLP; Expt. 2) were used in the two experiments. In each experiment, birds were allocated to four treatments in a 2 × 2 factorial arrangement (with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
6
7
0
Order By: Relevance
“…The upregulation of GLUT1 may also be related to the host's strategy to transport more nutrients out of cells and lead to cell nutrient depletion and apoptosis. Additionally, a similar finding of downregulation of CAT2 and y+LAT2 with Eimeria infection has been previously reported ( Lin and Olukosi, 2021b ; Teng et al, 2021a ). However, the mechanism behind the observation is unclear.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The upregulation of GLUT1 may also be related to the host's strategy to transport more nutrients out of cells and lead to cell nutrient depletion and apoptosis. Additionally, a similar finding of downregulation of CAT2 and y+LAT2 with Eimeria infection has been previously reported ( Lin and Olukosi, 2021b ; Teng et al, 2021a ). However, the mechanism behind the observation is unclear.…”
Section: Discussionsupporting
confidence: 89%
“…The current experiment showed that the parasite challenge significantly upregulated gene expression of claudin-1 and JAM2. Similar changes in tight junctions have been reported in previous Eimeria challenge studies ( Lin and Olukosi, 2021a ; Teng et al, 2021b ). It has been demonstrated that upregulation of claudin-1 is elevated in inflammatory bowel disease conditions ( Poritz et al, 2011 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations